2022
DOI: 10.3390/genes13020267
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis Reveals Subdivision of Black Rats (Rattus rattus) in India, Origin of the Worldwide Species Spread

Abstract: In contrast to the detailed and globally extensive studies on the spread of the commensal black rat, Rattus rattus, there has been relatively little work on the phylogeography of the species within India, from where this spread originated. Taking a genomic approach, we typed 27 R. rattus samples from Peninsular India using the genotyping-by-sequencing (GBS) method. Filtering and alignment of the FASTQ files yielded 1499 genome-wide SNPs. Phylogenomic tree reconstruction revealed a distinct subdivision in the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The history of Rattus colonization in the world is the history of human migrations; consequently, the origin of commensalism in these rodents inevitably reflects the history of human settlement and associated anthropogenic factors. Although further studies are needed, the more recent dispersal of R. norvegicus from its center of origin in Siberia to Europe in the 16th century [40] may be one of the reasons for the lower average value of genetic diversity found in our metadata, compared to the dispersal of R. rattus, which is linked to the beginning of Indian civilization (approximately 5000 years BC) and subsequent dispersal dynamics, mainly by maritime routes [35]. Other evidence supporting this behavior of a higher average value of genetic diversity in R. rattus than in R. norvegicus was found in two studies with a comparative phylogeography approach to that reported in our study.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The history of Rattus colonization in the world is the history of human migrations; consequently, the origin of commensalism in these rodents inevitably reflects the history of human settlement and associated anthropogenic factors. Although further studies are needed, the more recent dispersal of R. norvegicus from its center of origin in Siberia to Europe in the 16th century [40] may be one of the reasons for the lower average value of genetic diversity found in our metadata, compared to the dispersal of R. rattus, which is linked to the beginning of Indian civilization (approximately 5000 years BC) and subsequent dispersal dynamics, mainly by maritime routes [35]. Other evidence supporting this behavior of a higher average value of genetic diversity in R. rattus than in R. norvegicus was found in two studies with a comparative phylogeography approach to that reported in our study.…”
Section: Discussionmentioning
confidence: 72%
“…rattus and R. norvegicus are arguably the most successful invasive species on the planet, and human migrations have had a major influence on the spread and dispersal of invasive species populations within and between urban areas through processes such as genetic drift and gene flow [33,34]. Human movements and transportation networks can facilitate the dispersal of rats across urban environments, which can increase gene flow between populations and impact the genetic diversity of populations at different scales [31,[35][36][37]. For example, while [19], using SNPs, found divergent genomic signals in R. norvegicus in New York City at a scale of less than 600 m between colonies, Ref.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations